Traditional knowledge and phytochemical screening of plants used in snakebite prevention in Benin - Dossou, Ayékotchami Jacques (2023)
A total of 294 experienced respondents, including 238 traditional healers (traditional medicine practitioners) and 56 hunters, were interviewed in this study. The population under study is made up of people from 17 socio-cultural groups. The Nagots (12.59%), Mahis (8.84%), Adjas (8.50%), Baribas (7.82%) and Yoruba (7.14%) were the most represented. More than half of the interviewed traditional medicine practitioners were over 50 years old, with a mean age of 51 years. The age of the respondents ranged from 10 to 105 years (Table 2). Two respondents were less than 20 years, and these were included because they were known to have proven knowledge of the use of plants in snakebite management. Majority of respondents in this study were men (98.30%). Majority of the respondents were illiterate (51.02%) followed by those who had the chance to go to primary school (37.07%) while the remaining percentage had gone beyond primary education. About 82% of the people surveyed drew their knowledge from experiences of parents or relatives to prescribe medicinal plants followed by learning which represents only 14%. On the other hand, research, dreams and intuition are very little used modes of transmission and acquisition of endogenous knowledge.